Solar Energy - D Rugescu, Radu (IntechOpen, 2010)
The present "Solar Energy" science book hopefully opens a series of other first-hand texts in new technologies with practical impact and subsequent interest. They might include the ecological combustion of fossil fuels, space technology in the benefit of local and remote communities, new trends in the development of secure Internet Communications on an interplanetary scale, new breakthroughs in the propulsion technology and others. The editors will be pleased to see that the present book is open to debate and they will wait for the readers' reaction with great interest. Critics and proposals will be equally welcomed.